2015
DOI: 10.1093/bja/aeu318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prehabilitation on objectively measured physical fitness after neoadjuvant treatment in preoperative rectal cancer patients: a blinded interventional pilot study

Abstract: 01325909.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
345
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(361 citation statements)
references
References 36 publications
(18 reference statements)
8
345
1
2
Order By: Relevance
“…Integrated care delivery models, such as enhanced recovery after surgery programmes, have already confirmed the possibility of significantly improving clinical and functional outcomes in elderly and high‐risk patients60, 61, 62. In this situation, despite limited evidence, prehabilitation programmes, including preoperative optimization of coexisting chronic disease therapy, nutritional status, physical function and physiological support63, 64, 65, may represent a more comprehensive and effective opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated care delivery models, such as enhanced recovery after surgery programmes, have already confirmed the possibility of significantly improving clinical and functional outcomes in elderly and high‐risk patients60, 61, 62. In this situation, despite limited evidence, prehabilitation programmes, including preoperative optimization of coexisting chronic disease therapy, nutritional status, physical function and physiological support63, 64, 65, may represent a more comprehensive and effective opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective pilot trial was performed as a nested sub-study within a larger trial [22] approved by the North West -Liverpool East Research and Ethics Committee (11/H1002/12) and registered with ClinicalTrials.gov (NCT01325909). Written informed consent was obtained from all patients.…”
Section: Patients and Study Designmentioning
confidence: 99%
“…Nine studies were identified and underwent full text review [14][15][16][17][18][19][20][21][22] (Figure 1). One hundred and twenty two studies were identified from the initial literature search and twenty-one from handsearching the study references and through other sources.…”
Section: Description Of Included and Excluded Studiesmentioning
confidence: 99%